Calcific tendinitis of the supraspinatus tendon treated with iontophoresis: a case report - Sarvenaz Karimi-GhasemAbad; Alireza Rahmanizad (Journal of Current Oncology and Medical Sciences)
Introduction: In particular, calcium hydroxyapatite crystals that are frequently deposited within the supraspinatus and infraspinatus tendons are the cause of calcific tendinitis of the shoulder, an acute or chronic painful condition brought on by calcific deposits inside or around the rotator cuff tendons. Case presentation: A 46-year-old patient arrived at the clinic complaining of excruciating pain and significant movement impairment. Calcific tendonitis was diagnosed during a clinical assessment. Iontophoresis using a 5% acetic acid solution was applied three times a week for ten sessions as part of the treatment. Discussion: Various studies have identified 5% acetic acid iontophoresis as an effective intervention for calcific tendinitis-associated pain. Additionally, this treatment modality was partially responsible for the reduction in calcific deposits. Conclusion: Ten sessions of iontophoresis therapy using a 5% acetic acid solution were conducted. Following completion, there was a full recovery of shoulder range of motion, a complete clearance of calcific deposits, and no pain.